Evaluating the book of sentences and activities for kindergarten children from the point of view of female teachers in the city of Baghdad (Journal of the College of Education for Women, 2025)
The current study aimed to identify the evaluation of the book of experiences and activities for kindergarten children from the point of view of female teachers of the First Rusafa Education Directorate / Baghdad, and in light of the variables (educational qualification, number of years of service, the research sample consisted of (100) kindergarten teachers, the research followed the method Descriptive, the researcher used a questionnaire as a tool for data collection, which included (32) items distributed from four fields. Under each field, there are paragraphs related to that field, which are (educational objectives, content, educational strategies and means, artistic direction). Cronbach, mean, standard deviation, frequencies, percentage, t-test and analysis of variance The results of the study showed the following: Kindergarten teachers' assessments came with a moderate degree in the field of (strategies and teaching aids, and in the field of content), and they came with a high degree of appreciation in the field of (educational goals and the field of artistic direction).And there are no statistically significant differences at a significant level (0.05) between the means of evaluating the book of experiences and activities for kindergarten children from the point of view of female teachers according to the variable (educational qualification and years of service).